Characterization of different genetic classes of maize cultivated in a semi-arid region regarding the forage potential - Silveira, Eduarda Santos; Carvalho, Maisa Nascimento [UNESP]; De Lima, Beatriz Barreto; De Oliveira, Tâmara Rebecca Albuquerque; De Oliveira, Gustavo Hugo Ferreira (FapUNIFESP (SciELO), 2021)
Corn is widely grown in the semi-arid region and contains high energy value in the animal diet. Thus, the aim of this study was to characterize different genetic classes of maize cultivated for forage potential in the semi-arid conditions the Sergipe. For this, 36 genotypes were evaluated in incomplete blocks in lattice square re-ticulate 6x6, with two replications, in the experimental farm of Embrapa - Semiárido, in Graccho Cardoso-SE. The variables analyzed were: Plant height, stem diameter, plant weight, fresh weight, dry weight, percentage of dry weight and forage weight. With the data obtained was accomplished an analysis of variance with the help of software SAS 9,4 and, for generation the principal component analysis (PCA) and graphics, was used the software R with the package “GGEBiplotGUI”. All the variables showed significant differences between genetic classes. The first two main components included 83.9% of the total variation. The eigenvalues of the first PC (PC1) were 4,11, considering more significant, since the sum of all was of 6,99. The percentage of dry mass, stem diameter, plant weight, fresh, dry and forage mass obtained greater hability to discriminate genotypic classes. The intervarietal hybrids were closer to the “ideal” genotype. The greatest positive correla-tion was between forage weight and dry weight. The single and triple hybrids stood out individually in plant height and percentage of mass. The dry and forage mass obtained higher averages in all classes, except for simple hybrids. The varieties were the least stable in the evaluations. The intervarietal hybrids showed great-er forage potential and the double, topcross and varieties had greater genetic variability, already to the genetic classes they are not indicated for farmers of low and mean tech in the semiarid region for forage of maize.
Caracterização de diferentes classes genéticas de milho cultivados em região semiárida quanto ao potencial forrageiro
Keywords: Drought; Forage; Plant breeding; Silage production; Zea mays L